2015
DOI: 10.1590/so100-720320150005462
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity associated with progression of cervical lesions in a group of Colombian patients

Abstract: PURPOSE To analyze the relation between the cytological findings and telomerase activity (TA). METHODS Cervical samples were evaluated and classified according to the Bethesda System. Telomerase activity was measured total product generated values (TPG) using the TRAP assay (telomeric repeat amplification protocol); data were analyzed statistically using the χ2 test, with the level of significance set at p<0.05. RESULTS The study was conducted on 102 patients. Of these, 3.9% showed normal cytological findings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…TA was detected in 76% of the cases studied, and in 21.1% of the controls. These results are in agreement with previous studies which have detected TA in cancer and precancerous lesions while showing undetectable or low TA levels in normal tissue ( 12 , 13 ). Similar results were observed for the detection of HPV DNA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…TA was detected in 76% of the cases studied, and in 21.1% of the controls. These results are in agreement with previous studies which have detected TA in cancer and precancerous lesions while showing undetectable or low TA levels in normal tissue ( 12 , 13 ). Similar results were observed for the detection of HPV DNA.…”
Section: Discussionsupporting
confidence: 93%
“…Identifying molecular markers that will permit diagnosis and prognosis of women who have cervical lesions as well as predicting which precursor lesions are likely to become cancerous will lead to improvements in cervical cancer prevention. Several studies on women with normal cytology and/or different grades of cervical lesions have shown increased TA in higher grade lesions ( 10 13 ). Some studies have also shown that infections with HPV 16 and 18 are associated with increased TA ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Duque et al, had similar results by TRAP assay regarding the telomerase activity in range from 75.4 % in LSIL to 100% in HSIL, ASC-H and cervical cancer [37].…”
Section: Saretzki Et Al Found No Correlation Between the Telomerase mentioning
confidence: 66%
“…[33,34]. Published studies on the subject reveal that hTERT expression and telomerase activity was reported in 91.3%, 96.5% and 100% of cervical cancer samples [35][36][37]. Increased hTERT expression was also seen in 55.0% of CIN II and 82.1 % of CIN III diagnosed [38].…”
Section: Discussionmentioning
confidence: 91%
“…Telomeres, the terminal structures of chromosomes, are composed of long, repetitive 6-base pair nucleoproteins. Their vital role is to maintain chromosomal integrity and genomic stability by blocking the end-to-end fusion of chromosomes, nuclease degradation, and incomplete replication during cell division [1,2]. In human somatic cells, the average length of telomeres is 10-15 kb, and telomeric DNA is shortened during each cell division by approximately 50-200 base pairs [3,4].…”
Section: Introductionmentioning
confidence: 99%